Newer Behaviour Management Techniques in Children - Sonu Acharya1 , Susant Mohanty2 , Sheetal Acharya3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Children are not miniature adults. They should be treated as a different entity and not just as adults who areshortened. Children have their apprehensions and fear. The most commonly encountered is the fear of theunknown. This is something that is innate, inborn. Fear of dentistry is there in every individual, whetheryoung or old. This is mostly subjective. Children show exaggerated fear for dentistry as this is somethingnew to them. The pediatric dentists are trained in behavior management for reducing fear. There have beenmany method, both pharmacological and non-pharmacological for behavior management in children. Butwith changing times, we know that Child’s behavior has also undergone a sea change. Here we discuss somenewer behavior management techniques, recently introduced and included in our guidelines.